Seroma formation after parotidectomy: incidence, risk factors, and clinical implication - Kim, Joo Hyun (Frontiers in Surgery, 2026)
BackgroundPostoperative seroma is an underrecognized but clinically relevant complication after parotidectomy, leading to repeated aspirations and patient discomfort. Limited evidence exists on its incidence, risk factors, and clinical course.MethodsWe retrospectively reviewed 527 patients who underwent parotidectomy between 2020 and 2025. Demographics, tumor characteristics, surgical details, and postoperative variables were analyzed. Seroma was defined as fluid accumulation requiring aspiration without evidence of salivary fistula. Persistent seroma was defined as requiring multiple aspirations or persisting beyond 14 days after drain removal. Multivariate logistic regression was performed to identify independent predictors, and subgroup analyses were conducted for persistent seroma.ResultsSeroma occurred in 10.6% of patients. Independent risk factors included anterior tumor location (OR 2.21), larger tumor size (OR 1.58 per cm), body mass index ≥25 (OR 1.76), and use of facelift-type incisions (OR 1.92). Among patients with seroma, 33.9% developed persistent seroma, which was associated with larger tumors, higher BMI, greater aspirated volumes, and longer resolution times. Higher drain output prior to removal was also observed in the seroma group, suggesting that current thresholds for drain removal may be insufficient in high-risk patients.ConclusionAnterior tumor location, larger tumor size, elevated body mass index, and facelift-type incisions are significant predictors of postoperative seroma after parotidectomy. Risk-adapted strategies, such as individualized drain removal protocols and early use of compression dressings, may reduce seroma-related morbidity.